Correction: Practice makes better? The influence of increased practice on task conflict in the Stroop task. - Najenson, Jonathan; Zaks-Ohayon, Rut; Tzelgov, Joseph; Fresco, Nir (Memory & Cognition, 2025)
The article examines the impact of increased practice on task conflict in the Stroop task, a psychological test that measures cognitive control and attention. It discusses how varying levels of practice can influence performance and conflict during the task, providing insights into cognitive processes involved in managing conflicting information. The findings contribute to the understanding of how practice affects cognitive tasks and may have implications for strategies in educational and therapeutic settings. The article is available under a Creative Commons Attribution 4.0 International License, allowing for broader access and use.